Evaluation of process performance and retained sludge properties of a psychrophilic UASB reactor for treatment of iso-plophyl alcohol (2-propanol)-containing wastewater. Issue 13 (10th November 2018) - Danshita, Tsuyoshi; Miyaoka, Yuma; Sumino, Haruhiko; Iguchi, Akinori; Yamaguchi, Takashi; Syutsubo, Kazuaki
Abstract: In this study, a continuous feeding experiment was conducted with synthetic iso-plophyl alcohol (2-propanol)-containing wastewater using a lab-scale psychrophilic UASB reactor to evaluate process performance and retained sludge properties. For smooth acclimation, methanogenic granular sludge was seeded and a proportion of 2-propanol in the synthetic wastewater containing sucrose and volatile fatty acids was increased stepwise from 0% to 30%, 60% and then 90% of COD (chemical oxygen demand). As a result, after a 4-week period for acclimation to 2-propanol degradation, a COD removal rate of 95% was achieved at an organic loading rate (OLR) of 8.4 kg COD/m 3 /day. Additionally, the physical properties of the retained granular sludge were maintained even when the reactor was supplied with 2-propanol-rich wastewater for more than 200 days. From the batch assays using serum bottles, methanogenic degradation of 2-propanol was observed with acetone accumulation. By comparison, 2-propanol degradation was clearly inhibited in the presence of chloroform as a specific inhibitor of methanogen. A domain archaeal community structure analysis targeting 16S rRNA genes showed the relative abundance of the genus Methanospillium was increased in the 2-propanol acclimated sludge. These results suggested Methanospillium related species in the granular sludge appreciably contributed to the direct degradation of 2-proapanol into acetone under an anaerobic condition.